2014
DOI: 10.1007/s10067-014-2487-4
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening complications of adult-onset Still’s disease

Abstract: Adult-onset Still's Disease (AOSD) since its description in 1971 has proven to be a very complex and challenging disease entity. This rare auto-inflammatory disease is classically described by the "Still's triad" of fever, rash, and arthritis, although the atypical cases frequently outnumber the typical ones. The exact pathogenesis and etiologic factors responsible for the clinical features remain largely obscure, despite recent suggestive cytokine biology findings. Diagnosis is made on clinical grounds, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 89 publications
3
132
1
6
Order By: Relevance
“…Furthermore, overt reHLH has been shown to complicate 7-10 and 12-17 % of sJIA and AOSD, respectively [15,24,71]. Evidence for occult reHLH in a substantial proportion of patients with sJIA or AOSD (up to 50 %) supports the possibility that HLH and sJIA/AOSD could represent a continuum of severity [72,73].…”
Section: The Hemophagocytic Lymphohistiocytosis Hypothesismentioning
confidence: 97%
“…Furthermore, overt reHLH has been shown to complicate 7-10 and 12-17 % of sJIA and AOSD, respectively [15,24,71]. Evidence for occult reHLH in a substantial proportion of patients with sJIA or AOSD (up to 50 %) supports the possibility that HLH and sJIA/AOSD could represent a continuum of severity [72,73].…”
Section: The Hemophagocytic Lymphohistiocytosis Hypothesismentioning
confidence: 97%
“…Recently, Efthimiou et al [33] identified some unfavorable prognostic markers of disease, which should make the clinicians aware of a possible negative evolution. Such cases are more prone to become refractory to treatment over the course of disease.…”
Section: Severe Course and Life-threatening Complicationsmentioning
confidence: 99%
“…The most frequent complications of the disease were disseminated intravascular coagulation, macrophage activation syndrome (MAS), acute respiratory distress syndrome, myocarditis (sporadically complicated by cardiac tamponade) and liver failure. In general, MAS is one of the most feared life-threatening complications with a reported mortality rate ranging between 10 and 22% [33]. MAS should be increasingly suspected in light of the presence of high fever, lymphadenopathy, hepatosplenomegaly, pancytopenia, high serum levels of ferritin, triglycerides and liver enzymes but with normal erythrocyte sedimentation rate (ESR).…”
Section: Severe Course and Life-threatening Complicationsmentioning
confidence: 99%
“…A few cases have been reported in the literature in which AOSD manifested with atypical cutaneous features, causing a delay in diagnosis (6, 7 ). In some cases, this led to serious complications such as HLH, disseminated intravascular coagulopathy, thrombotic thrombocytopenic purpura, diffuse alveolar hemorrhage, and pulmonary arterial hypertension (8 ).…”
Section: Adult-onset Still Diseasementioning
confidence: 99%